Validación de una encuesta para medir la satisfacción de los médicos residentes sobre el programa de especialización en Lima, Perú. - Cabello, Emilio; Cabello, Almendra; Martínez, Melissa (Revista Medica Herediana)
Objective: To validate a survey aimed at measuring satisfaction of residents about a specialization program in Lima, Peru. Methods: A cross-sectional study was carried-out. The survey was built considering resident´s opinions on the satisfaction requirements of each program and the five components of the SERVQUAL quality survey. A pilot study was undertaken to evaluate the degree of understanding of the questions and an expert evaluation was also performed before applying the survey. Reliability was evaluated with Cronbach´s alpha test and validity was evaluated with a multifactorial analysis. Descriptive statistics was applied, Chi square test with a p value <0.05 was used. Results: 218 (82.0%) surveys were analyzed; 54.1% were females; 57.7% were younger than 30 years of age; 86.2% were of free position. Degree of understanding was 9.98 and time to complete the survey was 5.45 minutes. Cronbach´s alpha was 0.919. The factorial analysis of the five most important components of satisfaction explained 66.5% of the variance of the 22 questions. Overall satisfaction was 71.8%, reliability was 79.2%, ability to respond was 80.2%, security was 60.8%, empathy was 82.8% and tangible aspects was 55.9%. No difference by sex, age group, specialty and modality of admission was found. Conclusions: The survey tested showed to be reliable and valid to evaluate the satisfaction of residents to their programs and it is a useful tool to identify opportunities to improve the residency program.